Impact alternatives of the sustainable development of sugar cane products in the Colombian Los Llanos foothills - Monroy Ochoa, Néstor I.; Ruiz López, Adriana I.; Barajas Pardo, Diana; Pacheco Pérez, Camilo; Cárdenas García, Darío (Cooperativismo & Desarrollo, 2017)
Introduction: This research was carried out in the Los Llanos foothills subregion, which is located to the west of Meta (Colombia).Methodology: the population under study consisted of 71 productive units of sugarcane and raw cane sugar mills. Conglomerate sampling was applied. The qualitative and quantitative information was analyzed in the statistical program spss (v. 19).Results: The family units (father, mother and children) make up 77.14 % of the productive units of the sugar cane crop, which contributes to the improvement of crop yield, optimizes quality of life and food security of the peasant family. For the persistence of cultivation, generational turnover is required, since 78.57 % of cane workers are over 26 years old, and have low educational levels and scarce economic resources.Conclusions: The variety of products generated from the cultivation of sugar cane or raw cane crop represent an opportunity to diversify production and obtain food security. The population of municipalities with sugarcane production, on average has a better quality of life.
Keywords: associativity; sugarcane; conglomerates; food security; family unit